Analysis of the air temperature and relative humidity measurements in Budapest-Ferencváros - Pongrácz, Rita; Bartholy, Judit; Dezső, Zsuzsanna; Dian, Csenge (Hungarian Geographical Bulletin, 2016)
Ferencváros (9th district of Budapest) is one of the oldest districts among the 23 ones of the Hungarian capital. It is located near the river Danube in the southern central very heterogeneous part of the city, consisting of three- and four-storey old buildings, block houses with 4 or 8 levels, brownfi eld industrial areas, and large areas occupied by the railways system. Due to the functional and structural changes of special subsections of the district substantial local climatic changes occurred in the past few decades. The local government made efforts to complete several block rehabilitation programs already starting from the 1980s. Within the framework of these programs inner parts of the blocks were demolished, thus, inside the blocks more public green areas could be created. In order to evaluate the climatic conditions, we have recently initiated an in situ urban measurement program in the Inner Ferencváros and the rehabilitation zone. Air temperature and relative humidity where measured along a multi-site measuring path covering the target area, and continuously at a single site representative to the rehabilitation zone. Our measurements are compared to the regular meteorological data available from the Budapest-Pestszentlőrinc synoptic station. Our preliminary results are presented in this paper, which highlights the general characteristics of the urban environmental effects.